2017
DOI: 10.1111/joor.12514
|View full text |Cite
|
Sign up to set email alerts
|

Self‐report of temporomandibular joint clicking and psychological factors: is there an association?

Abstract: The objectives of this study were to test the hypothesis that self-reported TMJ clicking sounds in adolescents are positively associated with non-specific somatic symptoms, self-perception of body image and care-seeking behaviour. A cross-sectional study was carried out in 353 young adolescents (48·4% females) recruited from community (N = 272) and orthodontic clinic (N = 81) settings. Assessments included self-reported TMJ clicking, non-specific physical symptoms, body image concerns and for the clinic sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…TMJ clicking corresponds to 26.2% of clinical signs of TMD and is one of the most common complaints of patients 13 . Self-report of TMJ clicking are more frequent in care-seeking patients that also have greater non-specific physical symptoms, with a propensity to somatization and with the heightened awareness of their own body image 14 …”
Section: Introductionmentioning
confidence: 99%
“…TMJ clicking corresponds to 26.2% of clinical signs of TMD and is one of the most common complaints of patients 13 . Self-report of TMJ clicking are more frequent in care-seeking patients that also have greater non-specific physical symptoms, with a propensity to somatization and with the heightened awareness of their own body image 14 …”
Section: Introductionmentioning
confidence: 99%
“…Although impaired sleep quality can be present in the general adult population, 34 it is more frequent in TMD pain patients, and even more in those with dysfunctional pain 35 . The relationship between pain and sleep is a vicious cycle with mutual deleterious influences; a night of poor sleep is followed by a day with more intense and variable pain, which is then followed by a night of nonrestorative sleep and morning‐related complaints of unrefreshing sleep 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients with painless TMJ clicking also had higher PVAQ scores than the healthy control group, with T score mean higher than the normal range, although both groups had no pain (Table 2). Perhaps, this fact is based on the point that TMJ clicking was the main complaint for these individuals (patients with painless TMJ clicking), and higher levels of somatisation and excessive concerns with body image were reported in individuals who complain of joint sounds 34 . Yet, hypervigilance can also be regarded as a cognitive tendency, reflecting worry about health concerns 23…”
Section: Discussionmentioning
confidence: 99%
“…Besides the two mentioned factors, there are also indications that psychological factors play a role in the occurrence of TMJ sounds . In a recent study, it appeared that TMJ sounds in adolescents were associated with a propensity to somatization and concerns with body image . As both studies, however, made use of self‐reported information regarding the presence of TMJ sounds, it remains unknown whether the association between psychological factors and the presence of TMJ sounds also applies for studies that make use of objective assessments.…”
Section: Introductionmentioning
confidence: 99%
“…6 In a recent study, it appeared that TMJ sounds in adolescents were associated with a propensity to somatization and concerns with body image. 7 As both studies, however, made use of self-reported information regarding the presence of TMJ sounds, it remains unknown whether the association between psychological factors and the presence of TMJ sounds also applies for studies that make use of objective assessments. Therefore, this study aimed to evaluate the clinically determined prevalence of ADDR among children and adolescents and to evaluate potential risk indicators related to this.…”
Section: Introductionmentioning
confidence: 99%